2012
DOI: 10.1245/s10434-012-2578-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Appropriate Short-Term Mammographic Surveillance in Patients Who Undergo Breast-Conserving Surgery (BCS)

Abstract: Based on our data and the low expected yield of IBTR in the first 2 years, annual mammographic surveillance appears adequate following BCS and interval ipsilateral mammograms at 6 and 18 months do not provide additional clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…14 A third study concluded, after looking at their institutional experience, that the rate of ipsilateral breast cancer recurrence was extremely low during the first two years after BCT (two recurrences out of 375 patients), and the addition of interval ipsilateral mammograms at 6 months and 18 months provided no additional clinical benefit. 15 As another consideration, mammography is less sensitive in women with a history of breast cancer [65.4% (95% CI, 61.5-69.0%)], compared to those with no such history [76.5% (95% CI, 71.7-80.7%)]. 16 Sensitivity is also lower within the first five years after primary breast cancer treatment [60.2% (95%CI, 54.7%-65.5%)] compared to after 5 years from treatment [70.8% (95% CI, 65.4%-75.6%)].…”
Section: Discussionmentioning
confidence: 99%
“…14 A third study concluded, after looking at their institutional experience, that the rate of ipsilateral breast cancer recurrence was extremely low during the first two years after BCT (two recurrences out of 375 patients), and the addition of interval ipsilateral mammograms at 6 months and 18 months provided no additional clinical benefit. 15 As another consideration, mammography is less sensitive in women with a history of breast cancer [65.4% (95% CI, 61.5-69.0%)], compared to those with no such history [76.5% (95% CI, 71.7-80.7%)]. 16 Sensitivity is also lower within the first five years after primary breast cancer treatment [60.2% (95%CI, 54.7%-65.5%)] compared to after 5 years from treatment [70.8% (95% CI, 65.4%-75.6%)].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest benefit from biannual mammography for 2-5 years following treatment, while other studies and most major treatment guidelines (including ASCO and NCCN) support annual mammography following breast conservation therapy 15, 16. One retrospective study as well as a meta-analysis of surveillance mammography found no benefit to 6-month interval screening mammography while a recent retrospective single institution review suggested benefit from 5 years of biannual mammographic surveillance 12, 17-19.…”
Section: Monitoring Treatment Response In the Adjuvant Settingmentioning
confidence: 99%
“…Most researchers agree that regular surveillance mammography in women diagnosed with early stage breast cancer improves long-term outcomes; however, the optimal interval for mammographic follow-up is currently debated. Some studies suggest benefit from biannual mammography in the initial 2-5 years following treatment, while other studies and most major treatment guidelines (including ASCO and NCCN) support annual mammography following breast conservation therapy 6, 46, 47. One retrospective study and a meta-analysis of surveillance mammography found no benefit to semi-annual (6-month interval) screening mammography, while a recent retrospective single-institution review suggests a benefit from 5 years of semiannual mammographic surveillance 6, 48-50.…”
Section: Mammographymentioning
confidence: 99%
“…Multiple independent studies evaluation intermediate to high-risk populations demonstrate that the combination screening mammography with supplemental ultrasound resulted in a higher false-positive rate and a lower positive predictive value when compared to screening mammography alone 6, 46, 47, 56. Furthermore, in-situ cancers are often missed by sonography, and screening ultrasound is time intensive - often requiring direct physician supervision.…”
Section: Ultrasoundmentioning
confidence: 99%